ANALISIS DESKRIPTIF KECURANGAN YANG DILAKUKAN MAHASISWA DALAM PERTANGGUNG JAWABAN PENGGUNAAN DANA KEGIATAN MAHASISWA (DALAM KERANGKA TEORI FRAUD - Aisyah Assadiah Putri (Jurnal Ilmiah Mahasiswa FEB, 2017)
This study aims to explain the process of accountability report preparation of student activity funds and explain factors that affect student’s decision to commit acts of fraud in reporting the use of their funds. This research was conducted on students of Faculty "X" using descriptive qualitative method. In addition, Fraud diamond theory is used to determine factors of fraud. The result of this research indicates that students commit fraud by falsifying transaction proof and signature and doing mark-ups. Furthermore, the weakening of accounting substance is also one of the causes, together with financial pressure when students tries to improve the efficiency of their expenses and work relationships pressure between students and faculty leaders, which is not quite sustainable. In addition, the existing regulations about fund usage and its reporting are not relevant with the current condition. The opportunity factor arises due to the lenient leadership of faculty officials. Fraud committed by other institutions is also a factor that rationalize the students about the fraud they have committed. Finally, position in the institution and information and experience they have are the ability factor for the inappropriate conduct.Keywords: fraud, fraud diamond theory, responsibility reports